Shadow of a dark queen - Feist, Raymond E. (Feist, Raymond E. Serpentwar saga, 2011)
Two unlikely friends, Eric and Roo, take up arms to defend their native Midkemia against the terrible Emerald Queen and her gargantuan reptile army.